Introduction of multi-dose PCV 13 vaccine in Benin: from the decision to vaccinators experience - Daleb Abdoulaye Alfa; Roch A. Houngnihin; G. Patrick Ilboudo; Naomi Dick; Landry Kaucley; Téné-Alima Essoh (BMC, 2020)
Abstract Background In 2011, Benin introduced the 13-valent pneumococcal conjugated vaccine (PCV13), in a single-dose vial, into its Expanded Programme for Immunisation (EPI) with support from Gavi. In April 2018, with the support of the Agence de Médecine Préventive Afrique (AMP) and other technical and financial partners, the single-dose vial was transitioned to a four-dose vial. Here we describe the decision-making process and the experience of the vaccinators during the change. Methods We carried out semi-structured, individual interviews with 61 participants individuals involved in the EPI: 7 from central level, 5 from regional level, 7 from township level and 42 from district level. The interviews were recorded and transcribed, and the information categorised, using Nvivo software, and then analysed. Results The Inter-agency Coordination Committee (ICC), the Benin National Advisory Committee for Vaccines and Vaccination, (BNACVV) and the World Health Organisation (WHO) (i.e., the traditional governance structures involved in vaccination decisions) were not involved in the decision to change to the four-dose vial for PCV13. The decision was taken by the EPI, supported by Gavi. The vaccination errors observed in the first months following the change in presentation were due to the absence of guidelines for changes in vaccine presentation and the central-level actors' perception that it was 'only a change in the vial', and therefore that the communication and training for a new vaccine were not required since the vaccine itself and its administration mode were unchanged. Conclusions It is important that the other countries eligible for Gavi support that are about to change to the multi-dose vial PCV13 presentation learn from Benin's experience. The main lessons learned are that changes in the presentation of an established vaccine should follow the same process as the introduction of a new vaccine, and that all stakeholders involved in vaccines and vaccination should participate in the decision-making process and implementation.